2020
DOI: 10.1155/2020/8513070
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Bony Defects after Tumor Resection with 3D‐Printed Anatomically Conforming Pelvic Prostheses through a Novel Treatment Strategy

Abstract: There has been an increasing interest and enormous applications in three-dimensional (3D) printing technology and its prosthesis, driving many orthopaedic surgeons to solve the difficult problem of bony defects and explore new ways in surgery approach. However, the most urgent problem is without an effective prosthesis and standard treatment strategy. In order to resolve these problems, this study was performed to explore the use of a 3D-printed anatomically conforming pelvic prosthesis for bony defect reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…This reliance on 3D models of pre-curved plates to guide fracture repositioning provides a meaningful attempt to apply guide template technology to fracture repositioning [ 24 , 145 ]. Many other scholars have also made attempts to use adjunctive guides for different surgical procedures, such as personalized guided orthopedic guides and personalized bone defect repair guides [ 146 ], in order to allow more efficient and accurate solutions to difficult surgical problems [ 31 , 147 ].…”
Section: Basic Types and Clinical Applications Of Orthopedic 3d Print...mentioning
confidence: 99%
“…This reliance on 3D models of pre-curved plates to guide fracture repositioning provides a meaningful attempt to apply guide template technology to fracture repositioning [ 24 , 145 ]. Many other scholars have also made attempts to use adjunctive guides for different surgical procedures, such as personalized guided orthopedic guides and personalized bone defect repair guides [ 146 ], in order to allow more efficient and accurate solutions to difficult surgical problems [ 31 , 147 ].…”
Section: Basic Types and Clinical Applications Of Orthopedic 3d Print...mentioning
confidence: 99%
“…The outcome of patients with limb salvage reconstruction depends on the surgeon's clinical experience; therefore, different surgeons performing the procedure will lead to different outcomes (Table 3). 6,8,14,15,18‐24 In this study, we employed 3D printing, lesion models, osteotomy templates, and personalized pelvic prostheses for an integrated treatment of pelvic tumors and optimized design of the bone‐implant interface structure. Our study results showed that satisfactory early functional recovery and prosthesis survival rates were obtained based on patient prognosis, and early function.…”
Section: Discussionmentioning
confidence: 99%
“…There were nine patients with an excellent postoperative MSTS-93 lower limb functional score (>80%), eight with a good score (between 60% and 80%), and two with a fair score (between 40% and 3). 6,8,14,15,[18][19][20][21][22][23][24] In this study, we employed 3D printing, lesion models, osteotomy templates, and personalized pelvic prostheses for an integrated treatment of pelvic tumors and optimized design of the bone-implant interface structure. Our study results showed that satisfactory early functional recovery and prosthesis survival rates were obtained based on patient prognosis, and early function.…”
Section: Reconstruction Outcomes and Complicationsmentioning
confidence: 99%
“…Reconstructive options can prevent significant differences in leg length and preserve hip joint function [5]. Complications are frequent, however, including infection, prosthesis loosening and failure, and fractures of the remaining bone or allografts, when used [5,7]. The choice of a particular technique for hip joint reconstruction depends on prognosis, functional capabilities of the patient, and particular surgical scenario and type of resection.…”
Section: Introductionmentioning
confidence: 99%
“…With advances in implantation techniques, oncology surgeons have gradually adopted prosthetic reconstruction of the pelvis after tumor resection [ 7 ]. Reconstructive options can prevent significant differences in leg length and preserve hip joint function [ 5 ].…”
Section: Introductionmentioning
confidence: 99%